Implications of Covid-19 to the Construction Industry in Kelantan from Contractor’s Perspective. - BINTI OTHMAN, SITI KHADIJAH; SUSHILAWATI ISMAIL (Recent Trends in Civil Engineering and Built Environment, 2022)
The spread of the Covid-19 virus has affected the global economy, social and commercial activities. Therefore, the construction industry in Malaysia was also affected by this pandemic where construction activities have to be stopped due to movement control order (MCO) restriction. This situation has resulted in an economic recession to the local construction industry. Corresponding to this, the purpose of this study is to identify the factors that affect construction contractors due to the Covid-19 pandemic, particularly in the district of Kota Bharu, Kelantan. Besides, it was also aimed to analyze the challenges and implications of the Covid-19 pandemic on construction contractors. This study had interviewed 5 respondents from G7 class contractor companies around the district of Kota Bharu. This study has recognized 6 main factors that affected construction contractors throughout the pandemic includes project time, cost loss, manpower, productivity, supply of building materials and employers. The challenges faced by the contractors were also discussed in this paper. Overall, this study found that the pandemic has had a major impact on the local construction players. Perhaps, more strategic planning can be strategized by a construction contractors as a preparation to face such pandemic in the future.